Strategic Decision-Making: Research Mapping from Exploratory Factor Analysis and Multidimensional Scaling - Ivano Ribeiro (Contabilidade, Gestão e Governança, 2017)
To understand the connection between authors, concepts and theories that address strategic decision-making, in this article the citations and co-citations of works published up to 2014 were analyzed. The sample consists of 489 articles published in international periodicals included in the Web of Science-ISI Web of Knowledge database. The search was conducted using key words that enabled the identification of the highest possible number of articles on the subject in question. Through Multidimensional Scaling (MDS) and Exploratory Factor Analysis (EFA), the conceptual and theoretical relationships involved in these studies were identified. The results show that from 1980 to 2014 three different factors are highlighted: the first has to do with studies on conflict; the second factor is the Top Management Team (TMT) and decision-making; and the third is related to processes. More recently (2013-2014), studies on strategic decision-making are converging towards analysis of conflict and process, composition and control, with Upper Echelon Theory being maintained as the central theory in these studies. This finding is the main contribution of this article.